Can molecular projected density of states (PDOS) be systematically used in electronic conductance analysis? - Rangel, Tonatiuh; Rignanese, Gian-Marco; Olevano, Valerio (Beilstein Journal of Nanotechnology, 2015)
Using benzenediamine and benzenedithiol molecular junctions as benchmarks, we investigate the widespread analysis of the quantum transport conductance in terms of the projected density of states (PDOS) onto molecular orbitals (MOs). We first consider two different methods for identifying the relevant MOs: (1) diagonalization of the Hamiltonian of the isolated molecule and (2) diagonalization of a submatrix of the junction Hamiltonian constructed by considering only basis elements localized on the molecule. We find that these two methods can lead to substantially different MOs and hence PDOS. Furthermore, within Method 1, the PDOS can differ depending on the isolated molecule chosen to represent the molecular junction (e.g., with or without dangling bonds); within Method 2, the PDOS depends on the chosen basis set. We show that these differences can be critical when the PDOS is used to provide a physical interpretation of the conductance (especially when its value is small, as it happens typically at zero bias). In this work, we propose a new approach in an attempt to reconcile the two traditional methods. Although some improvements were achieved, the main problems remain unsolved. Our results raise more general questions and doubts on a PDOS-based analysis of the conductance.
Keywords: benzene-diamine; benzene-dithiol; DFT-Landauer; molecular electronics; nanoelectronics; quantum transport

(untitled) - Reed, M. A.; Zhou, C.; Muller, C. J.; Burgin, T. P.; Tour, J. M. (Science, 1997)

(untitled) - Xu, B.; Tao, N. J. (Science, 2003)

(untitled) - Park, H.; Park, J.; Lim, A. K. L.; Anderson, E. H.; Alivisatos, A. P.; McEuen, P. L. (Nature, 2000)

(untitled) - Venkataraman, L.; Klare, J. E.; Tam, I. W.; Nuckolls, C.; Hybertsen, M. S.; Steigerwald, M. L. (Nano Lett., 2006)

Electronic transport in mesoscopic systems - Datta, S. (Cambridge University Press, 1995)

Electrical transport in nanoscale systems - Di Ventra, M. (Cambridge University Press, 2008)

(untitled) - Kubo, R. (J. Phys. Soc. Jpn., 1958)

(untitled) - Greenwood, D. A. (Proc. Phys. Soc., London, 1958)

(untitled) - Landauer, R. (IBM J. Res. Dev., 1957)

(untitled) - Keldysh, L. V. (Sov. Phys. - JETP, 1965)

(untitled) - Danielewicz, P. (Ann. Phys., 1984)

(untitled) - Rammer, J.; Smith, H. (Rev. Mod. Phys., 1986)

(untitled) - Thygesen, K. S.; Jakobsen, K. W. (Chem. Phys., 2005)

(untitled) - Nitzan, A.; Ratner, M. A. (Science, 2003)

(untitled) - Toher, C.; Sanvito, S. (Phys. Rev. B, 2008)

(untitled) - Pontes, R. B.; Rocha, A. R.; Sanvito, S.; Fazzio, A.; da Silva, A. J. R. (ACS Nano, 2011)

(untitled) - Ferretti, A.; Mallia, G.; Martin-Samos, L.; Bussi, G.; Ruini, A.; Montanari, B.; Harrison, N. M. (Phys. Rev. B, 2012)

(untitled) - Quek, S. Y.; Venkataraman, L.; Choi, H. J.; Louie, S. G.; Hybertsen, M. S.; Neaton, J. B. (Nano Lett., 2007)

(untitled) - Darancet, P.; Widawsky, J. R.; Choi, H. J.; Venkataraman, L.; Neaton, J. B. (Nano Lett., 2012)

(untitled) - Dell’Angela, M.; Kladnik, G.; Cossaro, A.; Verdini, A.; Kamenetska, M.; Tamblyn, I.; Quek, S. Y.; Neaton, J. B.; Cvetko, D.; Morgante, A.; Venkataraman, L. (Nano Lett., 2010)

(untitled) - Cehovin, A.; Mera, H.; Jensen, J. H.; Stokbro, K.; Pedersen, T. B. (Phys. Rev. B, 2008)

(untitled) - Strange, M.; Rostgaard, C.; Häkkinen, H.; Thygesen, K. S. (Phys. Rev. B, 2011)

(untitled) - Rangel, T.; Ferretti, A.; Trevisanutto, P. E.; Olevano, V.; Rignanese, G.-M. (Phys. Rev. B, 2011)

(untitled) - Stadler, R.; Jacobsen, K. W. (Phys. Rev. B, 2006)

(untitled) - Stadler, R. (J. Phys.: Conf. Ser., 2007)

(untitled) - Stadler, R. (Phys. Rev. B, 2010)

(untitled) - Kastlunger, G.; Stadler, R. (Phys. Rev. B, 2013)

(untitled) - Bâldea, I. (Europhys. Lett., 2012)

(untitled) - Mera, H.; Niquet, Y. M. (Phys. Rev. Lett., 2010)

(untitled) - Mera, H.; Kaasbjerg, K.; Niquet, Y. M.; Stefanucci, G. (Phys. Rev. B, 2010)

(untitled) - Bâldea, I. (Nanotechnology, 2014)

(untitled) - Bâldea, I. (Faraday Discuss., 2014)

(untitled) - Shi, X. Q.; Dai, Z. X.; Zheng, X. H.; Zeng, Z. (J. Phys. Chem. B, 2006)

(untitled) - Gao, N.; Li, J. C.; Jiang, Q. (Appl. Phys. Lett., 2013)

(untitled) - Gutiérrez, R.; Grossmann, F.; Schmidt, R. (ChemPhysChem, 2003)

(untitled) - Sen, A.; Lin, C.-J.; Kaun, C.-C. (J. Phys. Chem. C, 2013)

(untitled) - Caliskan, S.; Laref, A. (Sci. Rep., 2014)

(untitled) - Kaliginedi, V.; Moreno-García, P.; Valkenier, H.; Hong, W.; García-Suárez, V. M.; Buiter, P.; Otten, J. L. H.; Hummelen, J. C.; Lambert, C. J.; Wandlowski, T. (J. Am. Chem. Soc., 2012)

(untitled) - Perrin, M. L.; Frisenda, R.; Koole, M.; Seldenthuis, J. S.; Gil, J. A. C.; Valkenier, H.; Hummelen, J. C.; Renaud, N.; Grozema, F. C.; Thijssen, J. M.; Dulić, D.; van der Zant, H. S. J. (Nat. Nanotechnol., 2014)

(untitled) - Strange, M.; Thygesen, K. S. (Beilstein J. Nanotechnol., 2011)

(untitled) - Ning, J.; Li, R.; Shen, X.; Qian, Z.; Hou, S.; Rocha, A. R.; Sanvito, S. (Nanotechnology, 2007)

(untitled) - Marzari, N.; Vanderbilt, D. (Phys. Rev. B, 1997)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Gonze, X.; Amadon, B.; Anglade, P.-M.; Beuken, J.-M.; Bottin, F.; Boulanger, P.; Bruneval, F.; Caliste, D.; Caracas, R.; Côté, M.; Deutsch, T.; Genovese, L.; et al. (Comput. Phys. Commun., 2009)

WanT, 2.5.0 (Ferretti, A.; Agapito, L.; Calzolari, A.; Buongiorno Nardelli, M.)

(untitled) - Calzolari, A.; Marzari, N.; Souza, I.; Buongiorno Nardelli, M. (Phys. Rev. B, 2004)

(untitled) - Müller, K.-H. (Phys. Rev. B, 2006)

(untitled) - French, W. R.; Iacovella, C. R.; Rungger, I.; Souza, A. M.; Sanvito, S.; Cummings, P. T. (J. Phys. Chem. Lett., 2013)

(untitled) - French, W. R.; Iacovella, C. R.; Cummings, P. T. (ACS Nano, 2012)

(untitled) - de Melo Souza, A.; Rungger, I.; Pontes, R. B.; Rocha, A. R.; Roque da Silva, A. J.; Schwingenschlöegl, U.; Sanvito, S. (Nanoscale, 2014)

(untitled) - Nguyen, H. C.; Szyja, B. M.; Doltsinis, N. L. (Phys. Rev. B, 2014)

(untitled) - Qian, X.; Li, J.; Yip, S. (Phys. Rev. B, 2010)

(untitled) - Sakuma, R. (Phys. Rev. B, 2013)

(untitled) - Agapito, L. A.; Ferretti, A.; Calzolari, A.; Curtarolo, S.; Buongiorno Nardelli, M. (Phys. Rev. B, 2013)

(untitled) - Lherbier, A.; Roche, S.; Restrepo, O. A.; Niquet, Y.-M.; Delcorte, A.; Charlier, J.-C. (Nano Res., 2013)